Preferensi dan Kecocokan Inang Pentalonia nigronervosa Coquerel (Hemiptera: Aphididae) terhadap Berbagai Varietas Pisang - Suparman Suparman; Nurhayati Nurhayati; Anita Setyawaty (Perhimpunan Entomologi Indonesia, 2011)
Pentalonia nigronervosa Coquerel (Hemiptera: Aphididae) is the only known vector of banana bunchy top virus (BBTV). The objective of this research was to study the preference and suitability of banana aphid P. nigronervosa to various banana genotypes. Survey conducted at Talang Betutu, South Sumatra indicates the existence of different preferences of the P. nigronervosa toward different varieties in the field. Host suitability test was conducted using 13 banana varieties that were invested with P. nigronervosa from taro plants. Preference test was conducted using a 200 cm x 200 cm x 150 cm mesh cage that were used to house 13 banana genotypes that were invested with P. nigronerosa. The numbers of aphids on different banana genotypes were observed. Result of the study showed that “kepok” genotype was more suitable for the growth of P. nigronervosa compared to other genotypes. The suitability was shown by higher population, faster population growth, lower mortality and the higher proportion of alate adults. Banana kepok infested with 20 aphids at the beginning of the test reached 324 individuals within 24 days with population growth rate of 8.27% per day, and produced 1.9% of alate imagoes appeared 6 days after infestation. Host preference test using the same genotypes suggested that the aphid prefer banana kepok more than to any other genotypes.